Linguistic-Conceptual Description of the Concept "Ta'na-Dashnom" in Uzbeki and English Languages - Ataboyev Isroiljon Mirza o‘g‘li (Genius Publishing Group, 2023)
Our article's analysis shows that the recipient may follow a standard set of points of view, which will react to the insult expressed both by the directive and by the representative and the commission. However, in each of the three cases, the ratio of these maximums is not the same. This allows us to assume that the response type of the recipient depends on the type of initial copy of the taste dashnom. Since the most common class of early copies formed with the semantics of condemnation of directive speech, we analyze them in our article.
Keywords: Concept; sxema; linguist; sinxron